Efficacy and safety of adjuvant EGFR-TKIs for resected non-small cell lung cancer: a systematic review and meta-analysis based on randomized control trials - Pengfei Zhao; Hongchao Zhen; Hong Zhao; Lei Zhao; Bangwei Cao (BMC Cancer, 2022)
Abstract Background Postoperative adjuvant cisplatin-based chemotherapy had been the standard care in patients with completely resected high-risk stage IB to IIIA non-small cell lung cancer (NSCLC) for decades. However, the survival benefits were far from satisfactory in clinical practice. Thus, this meta-analysis was performed to compare the efficacy and safety of adjuvant epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) in patients with resected NSCLC based on updated literature and research. Methods A systematic literature search based on random control trials (RCTs) was conducted with keywords on PubMed, Embase and the Cochrane library databases. All articles compared EGFR-TKIs to placebo or chemotherapy as adjuvant therapies for early-stage resected NSCLC. A meta-analysis was performed to generate combined hazard ratio (HR) with 95% confidence intervals (CI) for disease-free survival (DFS), overall survival (OS), and risk ratio (RR) with 95% CI for disease recurrence and adverse events (AEs). The Stata statistical software (version 14.0) was used to synthesis the data. Results A total of 9 RCTs comprising 3098 patients were included. Adjuvant EGFR-TKIs could significantly prolong DFS in patient with resected NSCLC harboring epidermal growth factor receptor (EGFR) mutations (HR 0.46, 95% CI 0.29–0.72), but had no impact on OS (HR 0.87, 95% CI 0.69–1.11). The subgroup analyses indicated that adjuvant EGFR-TKIs were superior in regard to DFS in most subgroups, including varied smoking status, EGFR mutations type, gender, age, Eastern Cooperative Oncology Group performance status and adenocarcinoma. Osimertinib resulted in decreased brain recurrence than first generation of EGFR-TKIs (RR 0.12, 95% CI 0.04–0.34 vs. RR 1.07, 95% CI 0.64–1.78, respectively). The AEs were generally manageable and tolerable. The incidence of high-grade (≥ 3) AEs including diarrhea (RR 5.68, 95% CI 2.94–10.98) and rash (RR 27.74, 95% CI 11.43–67.30) increased after adjuvant EGFR-TKIs treatment. Conclusions Adjuvant EGFR-TKIs therapy could significantly prolong DFS in patients with completely resected early-stage EGFR mutation-positive NSCLC, but had no impact on OS. Adjuvant EGFR-TKIs could be an important treatment option in patients with resected early-stage EGFR-mutant NSCLC.